Medication Adherence after Myocardial Infarction: The Impact of Anxiety and Depression - Khalaf Yousef Zubi, Arafat; Taye Hasan Al-jarrah, Laith; Elbert Alqsous, Najib; Wa’el Hindeyeh, Mohammad; Rateb Al sarayrah., Yazan (International Journal of Scientific Research and Management (IJSRM), 2023)
Medication Adherence after Myocardial Infarction: The Impact of Anxiety and Depression